Management Information System of Ummi Primary Clinic in Improving Service and Loyalty using WEB-based Customer Relationship Management - Tasmara, Salsabila; Harahap, Aninda Muliani (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The rapid development of science and technology plays a very important role in life, both in the fields of education, industry, business, tourism, entertainment and so on. To improve service quality, an effective information system is needed. This system serves to switch from manual methods to computerized systems. With the information system, the accuracy of the data stored can be guaranteed, thus reducing the possibility of errors when inputting data. Ummi Primary Clinic is one of the level I health facility clinics in Medan in providing health services to the community. To find out customer needs, customer relationship management (CRM) is needed to manage interactions with customers, and can improve service quality and loyalty to customers. The purpose of this research is to build a Management Information System for Ummi Pratama Clinic in Improving Services and Loyalty Using Web-Based Customer Relationship Management (CRM) to facilitate clinic owners and patients in order to improve the quality of services at Ummi Pratama Clinic. In this study, researchers adopted a descriptive qualitative approach method, the Waterfall Method was applied to structured research in building a software. Based on the results of the research, it can be concluded that this system is a web designed according to the needs of Ummi Pratama Clinic which is useful for managing clinic relationships with customers. The information generated by CRM is beneficial for the clinic and customers, because criticism, suggestions, needs and desires of customers can be well facilitated and become a motivation for the clinic to improve services for satisfaction.